The Influence of Professional Training and Work Motivation on Auditor Performance in the Regional Inspectorate of Palembang City - Adrian; Helmi, Sulaiman; Herdiansyah, M. Izman; Trisninawati (Indonesian Scientific Publication, 2025)
This study aims to investigate the impact of professional training on work motivation and auditor performance, focusing on the role of motivation as a mediating factor. The research employed a quantitative approach, using a survey method to collect data from auditors in various organizations. The data were analyzed using Structural Equation Modeling (SEM) to test the validity, reliability, and hypotheses. The findings indicate that professional training positively and significantly affects work motivation and auditor performance. Furthermore, work motivation significantly mediates between professional training and auditor performance. This study contributes to the literature by providing empirical evidence on the importance of professional training in enhancing work motivation and auditor performance. The results highlight the crucial role of motivation in achieving better performance outcomes